PENERAPAN STRATEGI INDEX CARD MATCH PADA MATA PELAJARAN IPS - Siddiq Dharmadi; Sudjarwo Sudjarwo; Darsono Darsono (Jurnal Studi Sosial / Journal of Social Studies, 2015)
This research aimed to improve the activity, motivation, and social studies student outcomes by applying active learning strategies type of index cards match. This research method was using classroom action research. The data were collected through observation sheet activity, motivation questionnaire, and test for learning outcomes. Results of research showed that the activity of motivation and student learning outcomes increase at each cycle. It was showed at the percentage of student learning activities in the first cycle of 45.83%, the second cycle of 57.64%, and the third cycle of 75.68%. For the percentage of students motivation in the first cycle of 65.5%, the second cycle of 72%, and the third cycle of 87.5%. While the percentage of students mastery learning in the first cycle there were 11 students (45.83%) were completed, the second cycle increased to 17 students (70.83%) were completed and increased on the third cycle to 19 students (79.17%) were complete.Penelitian ini bertujuan untuk meningkatkan aktivitas, motivasi, dan hasil belajar IPS siswa dengan menerapkan strategi pembelajaran aktif tipe index card match. Metode penelitian ini menggunakan penelitian tindakan kelas. Pengumpulan data dilakukan melalui lembar observasi aktivitas angket motivasi, dan soal tes untuk hasil belajar. Hasil penelitian menunjukkan bahwa aktivitas motivasi dan hasil belajar siswa meningkat pada setiap siklusnya. Hal ini terlihat pada persentase aktivitas belajar siswa pada siklus I sebesar 45,83%, siklus II sebesar 57,64%, dan siklus III sebesar 75,68%. Untuk persentase motivasi belajar siswa pada siklus I sebesar 65,5%, siklus II sebesar 72%, dan siklus III sebesar 87,5%. Sementara persentase ketuntasan belajar siswa pada siklus I terdapat 11 siswa (45,83%) yang tuntas, siklus II meningkat menjadi 17 siswa (70,83%) yang tuntas dan meningkat kembali pada siklus III menjadi 19 siswa (79,17%) yang tuntasKata kunci : aktivitas, hasil belajar, motivasi, strategi index card match